Implementasi Kriptografi Secret Sharing Scheme dan Steganografi Audio Least Significant Bit (LSB) - Alvira Firjan Humaira; Rini Marwati; Kartika Yulianti (JMT : Jurnal Matematika dan Terapan, 2023)
As long as communication technology continues to develop, information security becomes very important because crime in cyberspace is increasingly common. To improve information security, in this study a combination of secret sharing scheme (t, w) cryptography with the least significant bit (LSB) audio steganography was constructed. Secret sharing scheme cryptography is a modern cryptography that is able to prevent centralized information situations from occurring because it does not require a key for encryption. In addition, this method also makes it difficult for hackers to reconstruct messages because it is difficult to collect minimum shares. The implementation of this merger resulted in a prototype program using the Python 3.10 programming language with schema (3,4). The cover steganography media used is audio, and messages that can be processed by the program are a six-digit PIN number with a non-zero first digit. The results obtained from the encryption and embedding program are 4 pieces of audio-share which sound the same as the original audio, so that the existence of information in the audio is difficult to know. The result of the decryption and extracting program is a PIN that can be reconstructed.